A Note on the Perron Value of Brualdi-Li Matrices - Chen, Xiaogen (JOURNAL OF ADVANCES IN MATHEMATICS, 2016)
Let $B_{2n}$ denote the Brualdi-Li matrix, and let $ρ_{2n}=ρ(B_{2n})$ denote the Â Perron value of the Â Brualdi-Li matrix of order $2n$. We prove that is Â monotonically decreasing for all